An alternative methodology for the extraction of humic substances from organic soils - Rocha, Julio Cesar [UNESP]; Rosa, André Henrique [UNESP]; Furlan, Maysa [UNESP] (FapUNIFESP (SciELO), 1998)
The present study reports on an alternative methodology for the extraction of Humic Substances (HS) from the soil. The extractions were carried out with 0.5 M KOH for 3 h, at a ratio of 1:20 (m/v) under a nitrogen atmosphere. The HS were separated by centrifugation based on their solubility in alcaline solution. This methodology was compared with the usual procedure in three different soil samples and in one sample from vermicompost. The yield, E4/E6 ratio, ash content, and the elemental composition (C, H, O, N) of the extracted HS have been determined. The functional groups were identified by Fourier-transform infrared spectroscopy. This novel procedure adds a new perspective to the extraction of humic substances due to the short time and high performance of the extraction in relation to the usual procedure.
Keywords: Characterization; Extraction; Humic substances